Business in the heart of darkness : SOCO's oil exploration in the Virunga National Park - Morjaria, Ameet, (SAGE Business cases., 2021)
Emerging markets often are portrayed as dysfunctional and are characterized by weak institutions. Such environments can expose foreign direct investment to myriad challenges, including the demand for bribes, regulatory obstacles, government and business partner hold-up problems, macroeconomic meltdowns, and even civil war. This case underscores how non-market risk factors can have powerful implications on the success or failure of a business and must be monitored continuously and addressed with deliberate strategies.